Handling wireless of a robotic arm through the Kinect (Revista de Investigaciones Universidad del Quindío, 2013)
The implementation of robots from years ago has allowed improving the quality of human life by his replacement in activities that require repetitive or that have high degrees of difficulty. This work involves directing a robotic  arm whose functions are generated and transmitted wirelessly from a computer, the robot employee is within the classification of mobile robot manipulators. To generate the address of the arm is used as the Kinect motion recognition device, once they have made the proper processing of the captured information is transmitted wirelessly using the ZigBee technology to the robotic arm, comprising a system reception and microcontroller circuit which allows handling.
Keywords: Kinect; robotic arm; motion recognition; wireless transmission